Institutionalization of innovation transformations of agricultural production in the context of providing economic security - Pavlova, Galina; Павлова, Галина Євгеніївна; Honcharenko, Oksana; Гончаренко, Оксана Володимирівна; Yakubenko, Yuliya; Якубенко, Юлія Леонідівна (Чернігівський національний технологічний університет, 2018)
The article substantiates the importance of developing innovations in the agrarian sector to ensure the country's food security. The purposefulness of innovation development on the basis of implementing innovative policy tools leads to the introduction of regulatory, signalling and stimulating institutions. В статті обґрунтовується важливість розвитку інновацій в аграрній сфери для забезпечення продовольчої безпеки країни. Цілеспрямованість інноваційного розвитку на основі реалізації інструментів інноваційної політики зумовлює запровадження регулюючих, сигнальних і стимулюючих інституції.
Інституціоналізація інноваційних трансформацій агропромислового виробництва в контексті забезпечення економічної безпеки
Keywords: agro-industrial production; агропромислове виробництво; innovation; інновація; innovation development; інноваційний розвиток; innovation priorities; інноваційні пріоритети; institutionalization; інституціоналізація